PmrA/PmrB Two-Component System Regulation of lipA Expression in Pseudomonas aeruginosa PAO1 - Liu, Wu; Li, Menggang; Jiao, Liangcheng; Wang, Pengbo; Yan, Yunjun (Frontiers in Microbiology, 2018)
Pseudomonas lipases are well studied, but few studies have examined the mechanisms of lipase expression regulation. As a global regulatory protein, PmrA controls the expression of multiple genes such as the Dot/Icm apparatus, eukaryotic-like proteins, and secreted effectors. In this study, the effect of PmrA on expression of the lipase lipA in Pseudomonas aeruginosa PAO1 was investigated by knocking out or overexpressing pmrA, rsmY and rsmA. PmrA regulated the expression of lipA at both the transcriptional and translational level although translation was the pivotal regulatory mechanism for lipA expression. PmrA also regulated the expression of rsmY. Using gel mobility shift assay and pmrA/rsmY double gene knock-out model, we showed that PmrA directly bound to the promoter sequence of rsmY to regulate lipA expression. Translation of lipA was activated by the PmrA/PmrB system via RsmA. Specifically, the Shine-Dalgarno (SD) sequence located at lipA mRNA was overlapped through combination between RsmA and the AGAUGA sequence, subsequently blocking the 30S ribosomal subunit to the SD sequence, leading to translational inhibition of lipA. Transcriptional repression of RsmY initiated translation of lipA through negative translational regulation of rsmA. In conclusion, this study demonstrated that in P. aeruginosa PAO1, PmrA mainly regulated rsmY expression at a translational level to influence lipA expression. RsmY primarily activated lipA translation via negative translational regulation of rsmA.